2019
DOI: 10.1371/journal.pone.0220927
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in avian community composition in lowland conifer habitats at the southern edge of the boreal zone in the Adirondack Park, NY

Abstract: Climate change represents one of the most significant threats to human and wildlife communities on the planet. Populations at range margins or transitions between biomes can be particularly instructive for observing changes in biological communities that may be driven by climate change. Avian communities in lowland boreal habitats in the Adirondack Park, located at the North American boreal-temperate ecotone, have been the focus of long-term monitoring efforts since 2007. By documenting long-term changes in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Similarly, Glennon et al [50] found that boreal birds generally declined in occupancy at lowland boreal wetland sites in New York over a decade of observation, while non-boreal species were more likely to increase in occupancy. Further, non-boreal species were more likely to colonize sites that boreal species disappeared from, again indicating changes in community composition [50]. Ralston et al [42] combined 16 of these local and regional survey datasets to estimate population trends for 14 boreal bird species across the northeastern and upper Midwestern United States.…”
Section: Peripheral Populations Of Boreal Birds Are Genetically Unique Threatened By Climate Change and Decliningmentioning
confidence: 90%
See 4 more Smart Citations
“…Similarly, Glennon et al [50] found that boreal birds generally declined in occupancy at lowland boreal wetland sites in New York over a decade of observation, while non-boreal species were more likely to increase in occupancy. Further, non-boreal species were more likely to colonize sites that boreal species disappeared from, again indicating changes in community composition [50]. Ralston et al [42] combined 16 of these local and regional survey datasets to estimate population trends for 14 boreal bird species across the northeastern and upper Midwestern United States.…”
Section: Peripheral Populations Of Boreal Birds Are Genetically Unique Threatened By Climate Change and Decliningmentioning
confidence: 90%
“…Similarly, all species showed variation in trend estimates across surveys within each region. At a local scale, Glennon et al [50] also showed variation among sites in boreal bird community dynamics. Boreal birds were more likely to persist at sites with a greater amount of open Northern Peatland compared to sites with Boreal Upland Forest (habitat classifications following [9]).…”
Section: Peripheral Populations Of Boreal Birds Are Genetically Unique Threatened By Climate Change and Decliningmentioning
confidence: 99%
See 3 more Smart Citations